Uncommon renal tumors in children: A single center experience - Kartik Chandra Mandal; Madhumita Mukhopadhyay; Shibsankar Barman; Pankaj Halder; Biswanath Mukhopadhyay; Rajarshi Kumar (Wolters Kluwer Medknow Publications, 2016)
Aims: Scrutiny over the clinical behaviors, management, and the final outcome of some rare renal neoplasm in order to find out some hidden facts about these tumors which are playing an important role in the disease course and its management. Materials and Methods: Retrospective evaluation of uncommon (non-Wilms') renal neoplasm in the pediatric population in a tertiary care center. Fifteen cases of uncommon renal tumors were treated in our institution over the last 5 years (January 2008 to December 2012). The cases were tabulated in the form of age, sex, mode of presentation, preoperative investigations, intraoperative grading, pathological type, postoperative management and the final outcome. The patients were followed up for 2 years (clinically every 3 months and ultrasonography abdomen in every 6 months for first 2 years) in order to see any evidence of recurrence and complications related to postoperative chemotherapy. Results: Out of 15 cases, four cases were clear cell sarcoma (CCS) (26.6%), three cases were rhabdoid tumor (20%), three cases were congenital mesoblastic nephroma (20%), two cases were multilocular cystic nephroma (13.3%), two cases were renal teratoma (13.3%), and one case of teratoid Wilms' tumor (6.6%). There were two deaths (one CCS and one rhabdoid tumor) due to chemotherapy-related toxicity but no recurrence. Three patients were lost during postoperative follow-up; ten patients are doing well and getting a regular visit in the follow-up clinic. Conclusion: The clinical presentations of these uncommon renal tumors are similar to that of Wilms' tumor. Thus, preoperative diagnosis is difficult even with modern imaging techniques. Some of these tumors (CCS, rhabdoid tumor) are rapidly progressing and have a poor outcome. Hence, early intervention in the form of complete surgical resection of the tumor (whenever possible) and postoperative chemo/radiotherapy are imperative for fruitful outcome.